Review on the Worldwide Epidemiology of Uveitis. Issue 5 (September 2013) - Miserocchi, Elisabetta; Fogliato, Giovanni; Modorati, Giulio; Bandello, Francesco
Purpose: We describe the worldwide epidemiology of uveitis through a systematic literature review . Methods: Data obtained from the most relevant studies published until November 2012 were reported . Results: Results of our research were structured in sections about the epidemiology of uveitis by anatomical location of inflammation (anterior, intermediate, posterior, and panuveitis), type of inflammation (infectious and noninfectious), and by age (children and elderly). Difficulties encountered analyzing the different epidemiologic studies were discussed in a dedicated section . Conclusions: Limited information is available regarding the epidemiology of uveitis. Worldwide epidemiologic studies may help the clinician in the management of patients with inflammatory ocular diseases, enabling the comparison of different uveitis entities .